2021
DOI: 10.1039/d1mh01556g
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional ferroelectric metal for electrocatalysis

Abstract: The coexistence of metallicity and ferroelectricity has been an intriguing and controversial phenomenon as these two material properties are considered incompatible in bulk. We clarify the concept of ferroelectric metal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…[253] Obviously, the FE metals with electrically-tunable electronic states serve as a novel template for probing efficient electrocatalysis and electrochemical energy conversion. [202,254]…”
Section: Ferroelectric Metal Wtementioning
confidence: 99%
“…[253] Obviously, the FE metals with electrically-tunable electronic states serve as a novel template for probing efficient electrocatalysis and electrochemical energy conversion. [202,254]…”
Section: Ferroelectric Metal Wtementioning
confidence: 99%
“…We find that the ferroelectric phase is a semimetal, while the antiferroelectric phase is a semiconductor with a band gap of 0.7 eV. The semimetal nature of the ferroelectric phase is due to the built-in depolarization field that induces band bending 50,51 such that the valence band maximum (VBM) and the conduction band minimum (CBM) are dominated by the states of P − and P + surfaces, respectively (Fig. 3b).…”
mentioning
confidence: 93%
“…14,22 Computational studies have played critical roles in understanding the structure-performance relationship of ferroelectric catalysts as well as predicting the catalytic performance of heterogeneous catalysis and, more importantly, they can guide the search for catalysts with optimum performance before tedious trial-and-error experiments are conducted. 14,[23][24][25][26][27][28][29] For example, based on density-functional theory (DFT) calculations, Kou et al examined the photocatalytic water splitting performance of the 2D AgBiP 2 Se 6 monolayer. 24 It was found that the ferroelectric AgBiP 2 Se 6 monolayer is not favorable for the HER, yet it shows reactivity towards the oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%